ON THE RELIABILITY OF ESTIMATES OF THE AVERAGE CHEMICAL COMPOSITION OF THE UPPER CONTINENTAL CRUST AND RIVER DISCHARGE - Yaroshevskii A.A. (My University, 2007)
The classical problem of estimating the abundances of the chemical elements in the Earth’s crust is a challenge for geochemists. Its main complexity is related to the tremendous geochemical heterogeneity of the crust, which brings out the need to devise a method for the generalization of particular data that would provide a means to overcome this difficulty. Clarke and Washington used a method of simple computation of the average composition of igneous rocks, which were considered as the primary material of the Earth’s crust. Using geochemical balance arguments, Goldschmidt demonstrated that this estimate is in agreement with glacial deposits, which provided a basis for the first model of the chemical composition of the continental crust. Based on an expanded geochemical database and application of the principle of geochemical balance, Vinogradov and Taylor modified to some extent the values reported by Clark and Washington, which did not fundamentally change the general picture.